Alfonso Reyes: mexicano, intérprete do Brasil - Norte, Angela Lopes (2011)
This thesis discusses the literary and diplomatic production of Alfonso Reyes, a Mexican ambassador who lived in Brazil in the 1930s. His work is rich in texts that reflect his vision of the country, the Brazilian people, its history and cultural peculiarities. The analysis of the works produced in the period shows that the diplomat and the writer combined to produce accounts of the Brazilian reality that were transfigured into literature. Three axes guide this study: the Latin American intellectual and his utopian vision of America; the diplomatic documents analyzing the interim government and the early years of the constitutional government of Getúlio Vargas; and the essays, poetry and letters about the Brazilian beauties and peculiarities. To this end, the diplomat Alfonso Reyes is depicted as the epitome of the intellectual of Hispanic modernism by means of definitions of pan-Americanism, monroism, identity, Latinity, nation and intellectuality, as well as the conception of the essay as Latin American intellectual strategy in the search for identity. Alfonso Reyes s three contributions synthesis, homonoia and American intelligence to the utopian destination of America, his proposal to form an American community, supported by intellectuals of America, and the vision of Brazil as a peace-loving country are also discussed. Reyes s diplomatic ability is demonstrated in his notes to the Mexican government and in the decisive actions to increase Mexico-Brazil relations in the face of the revolution that maintained Vargas in power. His bias as a historian and universalistic and avant-garde writer is revealed in literary texts about utopian America, about Brazil and the Brazilians. It is also argued that, excluding some quotes from diplomats, few Brazilians are devoted to analyzing his work, which is practically unknown in Brazil, as well as the literary and official texts that marked his presence for nearly a decade in the city of Rio de Janeiro during the first half of the twentieth century. This study aims at proving that the twenty-first century requires the reading of his works and the inclusion of his name in discussions in the field of comparative literary and cultural studies in Latin America. It also aims at increasing the reading and the dissemination of the works of a diplomat-writer who labeled Brazil as a model of excellence among Latin American nations and made his speech be a means of negotiating his ideological project